Upper Trunk Brachial Plexus Palsy Following Chiropractic Manipulation - Cunningham, John; Hoskins, Wayne; Ferris, Scott (Frontiers in Neurology, 2016)
Introduction: Upper trunk brachial plexus palsy can result from high energy trauma and has never been reported following spinal manipulation. Background: The case is presented of a patient who developed an acute brachial plexus upper trunk palsy following spinal manipulative therapy. Discussion: Discussion is made on the incidence of complications following manipulation and recommendations to prospectively capture all serious complications. Concluding Remarks: Risks exist with spinal manipulative therapy. Neurological injury can occur. Risk assessment and re-examination should occur at every visit. Large rigorous prospective studies are required to identify the true incidence of serious complications resulting from manipulative therapy and the benefit:risk ratio.